Uma análise crítica dos métodos Suzuki e Sassmannshaus para o ensino do violoncelo: características e possibilidades de abordagem - Massa, Amanda Melo (2017)
This dissertation consists on a critical analysis of two methodologies on cello teaching for children from 4 to 10 years old, using the Suzuki Cello School method – which is employed worldwide – idealized by the Japanese violinist and educator Shinichi Suzuki (1898-1998), and the Sassmannshaus Early Start on the Cello method, applied in Europe, developed by the German violinist and educator Egon Sassmannshaus (1928-2010) coauthored by Kurt Sassmannshaus. This research was carried out using the methodology of Swanwick (2003; 2011; 2014), based on his analytical C(L)A(S)P model; Ilari (2003; 2011), which presents an overview, with a critical analyses on the philosophical and methodological aspects of the Suzuki method; Suzuki's own writings (2008), as well as the teaching material produced by the Suzuki Association of the Americas (1998; 2003); employing at the same time K. Sassmannshaus (2008; 2012), which details the methodological approach of the method; as also Menucci (2013), whose reflections on the principles of the left hand, based on the harmonic references, became relevant for the elaboration of our methodological proposal. The analysis of these two methods aims to present the potentialities of each one, enabling the identification, understanding, and discussion of possible gaps that can be filled through mutual complementations, thus contributing to the discussion of the teaching and learning process through the use of these two methods.